HUBUNGAN ANTARA JIWA WIRAUSAHA MAHASISWA DENGAN MOTIVASI, LINGKUNGAN KELUARGA DAN PENDIDIKAN PADA POLITEKNIK LP3I JAKARTA KAMPUS CIMONE - Rahayu Tri Utami (JURNAL LENTERA BISNIS, 2018)
ABSTRACT The more advanced a State the more people are educated, and many people are unemployed, the more it feels the importance of the entrepreneurial world. Development will be more successful if supported by entrepreneurs who can open employment because the ability of the government is very limited. The government will not be able to work on all aspects of development because it requires a lot of budget, personnel and supervision. Works and castes are only found in people who think creatively and innovative action for the creation of opportunities. The creative and innovative process usually begins with the emergence of ideas and thoughts to create something new and different. Something new and different is the added value of goods and services that become a source of excellence to be an opportunity.Entrepreneurship is an ability to create something new and different to be an opportunity and value added in the market through the process of managing resources in new and different ways.The sense of entrepreneurial ability is intended to know the extent to which students can be realized to be entrepreneur by looking at opportunities that exist in the environment. As the indicator factors are: Soul Entrepreneurship, Motivation, Environment, and Education. As a measuring tool in sensing the ability of students to business opportunities. The obstacle to note is that not all students can become entrepreneurs and succeed. It is necessary to have further handling to be able to find out more from the sensing. Keywords: Entrepreneurship, Student and Entrepreneurship.